Effects of Low Temperature Stress on Source–Sink Organs in Wheat and Phosphorus Mitigation Strategies - Xu, Hui; Hassan, Muhammad A.; Sun, Dongyue; Wu, Zhaochen; Jiang, Gang; Liu, Binbin; Ni, Qianqian; Yang, Wenkang; Fang, Hao; Li, Jincai; Chen, Xiang (Frontiers in Plant Science, 2022)
The 21st century presents many challenges to mankind, including climate change, fast growing human population, and serious concerns over food security. Wheat is a leading cereal crop that largely fulfills the global food needs. Low temperature stress accompanied by nutrient-starved soils is badly disrupting the source–sink relationship of wheat, thus causing an acute decline in final yield and deteriorating the grain quality. This review paper aimed to understand how low temperature stress affects wheat source–sink organs (i.e., leaves, roots, and spikes) and how phosphorus application reliefs in alleviating its harmful consequences. Also, we discussed mitigation strategies to enhance wheat capacity to adapt to varying temperature extremes and made rational recommendations based on modern agronomic and breeding approaches. Therefore, this study is likely to establish a solid foundation for improving the tolerance to low temperature stress and to improve its phosphorus utilization efficiency in wheat.